Die Entstehung des Sabbats Seine Bedeutung für Israels Zeitkonzept und Erinnerungskultur - Grund, Alexandra (Mohr Siebeck, 2011)
The Origins of the Shabbat. Its Significance for Israels Concept of Time and Culture of Remembrance.
PublicationDate: 20200518
Keywords: Sabbat -- Zeit -- Erinnerung -- Dekalog -- Altes Testament -- Array